Lacticaseibacillus casei SJRP38 and buriti pulp increased bioactive compounds and probiotic potential of fermented milk - Borgonovi, Tais Fernanda [UNESP]; Casarotti, Sabrina Neves; Penna, Ana Lúcia Barretto [UNESP] (Elsevier, 2021)
The effect of passion fruit and buriti pulps on probiotic and starter lactic acid bacteria growth and on fermented milk (FM) was evaluated. Buriti pulp showed higher amounts of lipids, total phenolic compounds (PC), β-carotene, lycopene and antioxidant activity (AA) than passion fruit. However, passion fruit was used more efficiently as a carbon source by all strains. Lacticaseibacillus casei SJRP38 showed the best results in the presence of passion fruit (1.8 log CFU/mL increase compared to the initial population) and the lowest reduction in the presence of buriti, thus it was selected to produce FM. Acidified milk (AM) with the same fruit pulps was used as a control. The buriti pulp did not affect the kinetic parameters of FM compared to the control. However, the addition of fruit pulps increased the PC in both FM and AM, and FM showed a greater increase (33.4–141.6%) than AM (21.4%–87.9%). Also, buriti pulp was able to increase (6–8%) the AA of the FM when compared to the AM. FM with buriti pulp stood out for its high amount of total PC, which indicates its high potential to be used as a functional food.
Keywords: Bioactive compounds; Fermented milk; Fruit pulp; Probiotic